Descriptive Study: Characteristics of Coastal Communities Regarding Disaster Preparedness - Anatolia K. Doondori; Irwan Budiana; Yustina P.M. Paschalia (Jurnal EduHealth, 2023)
Background: Flores Island is one of the areas with a fairly high level of disaster risk. Increasing the preparedness of coastal communities is important through disaster mitigation efforts that involve the community (community based disaster management), between sectors (Pentahelix), are sustainable and can reach all levels of society, especially communities that are vulnerable or at high risk of disaster. Research Objectives: This research aims to provide an overview of the characteristics of coastal communities regarding disaster preparedness in the Work Area of ​​the Ratu City Health Center, Ende Regency, East Nusa Tenggara Province (NTT). Method: The research design used in this research is descriptive with a cross sectional approach. The population in this study were coastal communities in the Kota Ratu Health Center, Ende Regency, East Nusa Tenggara Province (NTT) using a probability sampling technique using a simple random sampling approach, with a total sample of 41 respondents. Meanwhile, the instrument used in the data collection process in this research was a questionnaire sheet and the data analysis used was univariate analysis with data presented in narrative form, frequency distribution tables and percentages. Results: The results of the research show that the frequency distribution of all variables, namely the majority of knowledge preparedness, is good, namely 18 respondents (43.9%), the majority attitude preparedness variable is in the good category, 22 respondents (53.7%), the majority of the skills preparedness variable is in the good category, namely 19 respondents (46.3% ), the majority of policy preparedness variables are in the good category, namely 30 respondents (73.2%), the majority of emergency response plan preparedness variables are in the good category, namely 18 respondents (43.9%), the majority of disaster early warning system preparedness variables are in the good category, namely 26 respondents (63.4% ) and the majority of resource mobilization preparedness variables were in the good category, namely 20 respondents (48.8%). Thus, the frequency distribution of preparedness of coastal communities as a whole before intervention was given was that the majority were in the good and sufficient categories, namely 20 respondents each (48.8%). Conclusion: the attitude preparedness variable, policy preparedness and the early warning system preparedness variable are in the good category, above 50%.